A Numerical Study on the Bragg Resonance Characteristics of Multiple Floating Breakwaters - Weijie Liu; Zhengyang Luo; Miaohua Mao (Journal of Marine Science and Engineering, 2025)
This study investigates the Bragg resonance characteristics of multiple independently moored floating breakwaters and their wave attenuation performance using a computational fluid dynamics (CFD) model, OpenFOAM. The numerical framework is validated against experimental data for wave generation and floating body motion responses, demonstrating its reliable accuracy. Results show that Bragg resonance occurs in floating breakwater arrays, with the reflection coefficient peaking when the ratio of spacing to half-wavelength is an integer. Deeper immersion depth and longer boxes can enhance both Bragg reflection and energy dissipation by intensifying vorticity around the structures. Increasing the number of floating boxes marginally affects Bragg reflection but notably improves wave energy dissipation, primarily due to additional pontoons generating more turbulent motion. The optimal wave attenuation condition does not fully coincide with the peak Bragg reflection, highlighting the combined effect of reflection and dissipation of movable floating breakwaters. Future studies may further focus on the irregular wave conditions and impacts of the mooring system on the Bragg reflection and wave energy dissipation effect of multiple floating breakwaters.